Unraveling Azospirillum's colonization ability through microbiological and molecular evidence - Nievas, Sofia Mariela (2023)
It is known that members of the bacterial genus Azospirillum can promote the growth of a great variety of plants, an ability harnessed by the industry to create bioproducts aimed to enhance the yield of economically relevant crops. Its versatile metabolism allows this bacterium to adapt to numerous environments, from optimal to extreme or highly polluted. The fact of having been isolated from soil and rhizosphere samples collected worldwide and many other habitats proves its remarkable ubiquity. Azospirillum rhizospheric and endophytic lifestyles are governed by several mechanisms, leading to efficient niche colonization. These mechanisms include cell aggregation and biofilm formation, motility, chemotaxis, phytohormone and other signaling molecules production, and cell-to-cell communication, in turn, involved in regulating Azospirillum interactions with the surrounding microbial community. Despite being infrequently mentioned in metagenomics studies after its introduction as an inoculant, an increasing number of studies detected Azospirillum through molecular tools (mostly 16S rRNA sequencing) as part of diverse, even unexpected, microbiomes. This review focuses on Azospirillum traceability and the performance of the available methods, both classical and molecular. An overview of Azospirillum occurrence in diverse microbiomes and the less-known features explaining its notorious ability to colonize niches and prevail in multiple environments is provided.